System design for precise digitization and readout of the CSNS-WNS BaF2 spectrometer*Supported by National Research and Development plan (2016YFA0401602) and NSAF (U1530111). (February 2017) - Zhang 张, De-Liang 德良; Cao 曹, Ping 平; Wang 王, Qi 奇; He 何, Bing 兵; Zhang 张, Ya-Xi 雅希; Qi 齐, Xin-Cheng 心成; Yu 余, Tao 滔; An 安, Qi 琪
Abstract: The BaF2 (barium fluoride) spectrometer is one of the experiment facilities at the CSNS-WNS (White Neutron Source at China Spallation Neutron Source), currently under construction. It is designed to precisely measure the (n, γ ) cross section, with 92 crystal elements and complete 4 π steradian coverage. In order to improve the precision of measurement, in this paper, a new precise digitization and readout method is proposed. Waveform digitizing with 1 GSps sampling rate and 12-bit resolution is used to precisely capture the detector signal. To solve the problem of massive data readout and processing, the readout electronics is designed as a distributed architecture with 4 PXIe crates. The digitized signal is concentrated to the PXIe crate controller through a PCIe bus on the backplane and transmitted to the data acquisition system over gigabit Ethernet in parallel. Besides, the clock and trigger can be fanned out synchronously to every electronic channel over a high-precision distribution network. Test results show that the prototype of the readout electronics can achieve good performance and meet the requirements of the CSNS-WNS BaF2 spectrometer.